Beyond the News Media Logic? Analyzing the Social Media Orientation of University Leadership - Fürst Silke; Schäfer Mike S.; Vogler Daniel; Sörensen Isabel (Swiss Journal of Sociology, 2023)
Building on scholarship on the mediatization of organizations, we propose a conception of the social media orientation of organizational leaders and apply it to higher education. Based on an online survey of 276 leaders of Swiss higher education institutions, we show that social media platforms have made their way into university management and communication but are still not as important as news media. The study discusses differences between university types and uses the literature on new public management to derive influencing factors.